Integrating programme theory into the development of a core outcome set for technology-assisted counselling interventions in dementia: study protocol of the ProCOS study - Bauernschmidt, Dorothee; Wittmann, Janina; Bieber, Anja; Meyer, Gabriele (BMJ open, 2024)
IntroductionDue to the increasing number of persons with dementia, the need for family and professional support is growing. Counselling services aim to support family dementia caregivers and the use of information and communication technology may improve accessibility to counselling. The effectiveness of technology-based counselling in dementia remains unclear so far. Few randomised controlled trials have been conducted assessing heterogeneous outcomes. Theoretical underpinnings for the development and evaluation of these complex interventions were lacking in most cases. We therefore aim to formulate an initial programme theory of a technology-assisted counselling intervention for family dementia caregivers and to create the data basis for the consensus process of a core outcome set.Methods and analysisThe methodological approaches for developing a programme theory and a core outcome set will be integrated. In a scoping review, data on the characteristics, theoretical foundations of counselling interventions and outcomes of clinical studies will be collected. The lifeworld perception of relevant stakeholders on the importance of counselling in family caregiving will be explored in a phenomenological substudy using semistructured interviews. The synthesis of data from the literature review and the qualitative substudy will be performed by developing a logic model. Mechanisms of action and assumed causal relationships are explicated in the elements of programme theory (theory of change, outcomes chain and theory of action). An initial programme theory is then formulated. In addition, a ‘long list’ of outcomes and assessment instruments will be compiled.Ethics and disseminationThe ethics committee of the Medical Faculty of the Martin Luther University Halle-Wittenberg approved the study protocol (no. 2023–093).Findings will be reported to participants and the funding organisation and disseminated in peer-reviewed journals and at national and international conferences.Trial registration numberThe ProCOS (Development and evaluation of a technology-assissted counselling intervention for family caregivers of persons with dementia - Programme theory and preparation of a core outcome set) project is registered with the Core Outcome Measures in Effectiveness Trials initiative (https://www.comet-initiative.org/Studies/Details/2884).